2020
DOI: 10.1016/j.heliyon.2020.e05669
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of exosome purification methods using serum of Marek's disease virus (MDV)-vaccinated and -tumor-bearing chickens

Abstract: Marek's disease (MD) is an alphaherpesvirus (Marek's disease virus, MDV)-induced pathology of chickens associated with paralysis, immunosuppression, neurological signs, and T-cell lymphomas. MD is controlled in poultry production via live attenuated vaccines. The purpose of the current study was to compare methods for precipitating exosomes from vaccinated and protected chicken sera (VEX) and tumor-bearing chicken sera (TEX) for biomarker analysis of vaccine-induced protection and MD lymphomas respectively. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…These findings are similar to those observed for EV isolation with other polysaccharide heparin, which was found to co‐isolate a set of proteins not previously found to be associated with EVs (including centrosomal proteins, which we also identified for chitosan‐isolated material) (Balaj et al., 2015). Also, this is consistent with other reports that show that the characteristics of isolated EVs, including their size and cargo, can vary depending on the biophysical method used for their isolation (Nath Neerukonda et al., 2019; Neerukonda et al., 2020). EVs are considered promising vehicles for therapeutic applications because of their ability to penetrate and deliver therapeutic cargo across cell membranes and the blood‐brain barrier (Shahjin et al., 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are similar to those observed for EV isolation with other polysaccharide heparin, which was found to co‐isolate a set of proteins not previously found to be associated with EVs (including centrosomal proteins, which we also identified for chitosan‐isolated material) (Balaj et al., 2015). Also, this is consistent with other reports that show that the characteristics of isolated EVs, including their size and cargo, can vary depending on the biophysical method used for their isolation (Nath Neerukonda et al., 2019; Neerukonda et al., 2020). EVs are considered promising vehicles for therapeutic applications because of their ability to penetrate and deliver therapeutic cargo across cell membranes and the blood‐brain barrier (Shahjin et al., 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Both exosomes (30 to 150 nm) and microvesicles (100 to 1,000 nm) have a density of ∼1.1‐1.2 g/ml and are therefore difficult to separate from lipoproteins, which have a similar size and density (Brennan et al., 2020), when a biophysical property‐based method (e.g. ultracentrifugation, polymer‐mediated precipitation) is used for their isolation (Nath Neerukonda et al., 2019; Neerukonda et al., 2020). Therefore, many currently‐used EV isolation methods may co‐isolate contaminants, such as lipoproteins, or favour the isolation of a specific EV population based on the conditions used (Théry et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A significant disadvantage of commercial kits is their high cost, significant level of contamination of exosomes with nonexosomal components, and scaling limits. Meanwhile, some studies have shown that optimization of the standard PEG precipitation protocol (e.g., using PEG of different molecular weight and concentration, supplementing the protocol with additional washings and incubations) makes the procedure of exosome isolation even more efficient compared to commercial kits, though much cheaper [51][52][53][54]. In addition, this technique can be successfully used for isolation from large volumes of biofluid [50].…”
Section: Precipitation Techniquesmentioning
confidence: 99%
“…As viruses and extracellular vesicles (EVs) share biogenesis pathways, the EVs have recently been suggested as a potential source of viral antigens to elicit specific immune responses and develop new vaccination platforms [ 28 ]. However, the role of exosomes in the biology of avian herpesviruses has not been fully understood, although the exosomes from serum of MDV-vaccinated and tumor-bearing chicken had been previously isolated and primarily characterized by different approaches [ [29] , [30] , [31] ]. To investigate the role of exosomes carrying viral miRNAs in MDV-1 infection and MD tumorigenesis, we isolated exosomes from MDV-induced T lymphoma cell line MSB-1 [ 32 ].…”
mentioning
confidence: 99%